2017
DOI: 10.1002/ijc.31168
|View full text |Cite
|
Sign up to set email alerts
|

Administration of adjuvant chemotherapy for stage II‐III colon cancer patients: An European population‐based study

Abstract: The advantage of adjuvant chemotherapy (ACT) for treating Stage III colon cancer patients is well established and widely accepted. However, many patients with Stage III colon cancer do not receive ACT. Moreover, there are controversies around the effectiveness of ACT for Stage II patients. We investigated the administration of ACT and its association with overall survival in resected Stage II (overall and stratified by low-/high-risk) and Stage III colon cancer patients in three European countries including Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 39 publications
5
35
0
Order By: Relevance
“…The 5-year OS rates of MUA and NMUA were similar to previous report (19). More importantly, we showed again no survival difference between MUA and NMUA in stage II colon cancer, even in pT3 N0 M0 colon cancer with receipt of chemotherapy Despite clinical guidelines that had recommendations of adjuvant chemotherapy for high-risk colon cancer, the efficacy of adjuvant chemotherapy in high-risk disease had always been the subject of debate (22)(23)(24), indicating the necessity to identify candidates for adjuvant chemotherapy in stage II colon cancer. Few prior studies listed MUA as a high-risk factor.…”
Section: Discussionsupporting
confidence: 88%
“…The 5-year OS rates of MUA and NMUA were similar to previous report (19). More importantly, we showed again no survival difference between MUA and NMUA in stage II colon cancer, even in pT3 N0 M0 colon cancer with receipt of chemotherapy Despite clinical guidelines that had recommendations of adjuvant chemotherapy for high-risk colon cancer, the efficacy of adjuvant chemotherapy in high-risk disease had always been the subject of debate (22)(23)(24), indicating the necessity to identify candidates for adjuvant chemotherapy in stage II colon cancer. Few prior studies listed MUA as a high-risk factor.…”
Section: Discussionsupporting
confidence: 88%
“…[34] In addition to surgery, systemic therapy is an important treatment modality for regional CRC. [35] Studies have shown large variations in the use of adjuvant chemotherapy [36] and pre-operative radiotherapy [37] across countries. For example 56% of cases with Dukes' stage C colon cancers in the United States received chemotherapy while only 42% of cases with the same stage received chemotherapy in Northern Europe [38].…”
Section: Discussionmentioning
confidence: 99%
“…The role and efficacy of adjuvant chemotherapy for CRC have been well established. Modern chemotherapeutic regimens have been demonstrated to improve overall survival (OS), especially for stage II and III patients (3,4).…”
Section: Introductionmentioning
confidence: 99%